Effect of acid fruit juices combined with electric or sonic toothbrushing on root dentin permeability - An in vitro study - Batitucci, Roberta Grasselli [UNESP]; Zandim-Barcelos, Daniela Leal [UNESP]; Rocha, Fernanda Regina Godoy [UNESP]; Pinheiro, Michele Carolina [UNESP]; Fontanari, Lucas Amaral [UNESP]; Sampaio, José Eduardo Cezar [UNESP] (FapUNIFESP (SciELO), 2012)
The purpose of this in vitro study was to quantify the alterations on human root dentin permeability after exposure to different acid fruit juices and to evaluate the effect of toothbrushing with electric or sonic toothbrush after acid exposure. The root dentin of 50 extracted third molars was exposed with a high speed bur. Crowns were sectioned above the cementoenamel junction and root fragments were used to prepare dentin specimens. Specimens were randomly assigned to 5 groups according to the fruit juice (kiwifruit, starfruit, green apple, pineapple and acerolla). Each specimen was connected to a hydraulic pressure apparatus to measure root dentin permeability using fluid filtration method after the following sequential steps: I) conditioning with 37% phosphoric acid for 30 s, II) root scaling, III) exposure to acid fruit juices for 5 min and IV) electric or sonic toothbrushing without dentifrice for 3 min. Data were analyzed statistically by the Wilcoxon and Mann-Whitney tests at 5% significance level. All fruit juices promoted a significant increase of dentin permeability while toothbrushing decreased it significantly (p<0.05). It may be concluded that all acid fruit juices increased root dentin permeability, while toothbrushing without dentifrice after acid exposure decreased the permeability. The toothbrush mechanism (electric or sonic) had no influence on the decrease of root dentin permeability.
Keywords: Acidic beverages; Dentin; Toothbrushing